Réponses

Meilleure réponse !
2014-02-27T12:49:32+01:00
Bonjour

1) M = (2x - 3)² - (x + 5)(2x - 3)
       = (4x² - 12x + 9) - (2x² - 3x + 10x - 15)
       = 4x² - 12x + 9 - 2x² + 3x - 10x + 15
       = 2x² - 19x + 24

 2) M = (2x - 3)(2x - 3) - (x + 5)(2x - 3 )
       = (2x - 3) [(2x - 3) - (x + 5)]
       = (2x - 3) (2x - 3 - x - 5)
       = (2x - 3) (x - 8)

3) x = 3/2
M = (2x - 3) (x - 8)
    =  (2 * (3/2) - 3)(3/2 - 8)
    = (3 - 3)(3/2 - 8)
    = 0 * (3/2 - 8)
    = 0

x = 0
M = 2x² - 19x + 24
    = 2 * 0 - 19* 0 + 24
    = 0 - 0 + 24
    = 24